Determinant of exchange rate in Malaysia / Wan Muhammad Firdaus Wan Aman - Wan Aman, Wan Muhammad Firdaus (Faculty of Business and Management, 2016)
This paper investigates the factors that stimulate and maintain economic growth. The research is to analyze the relationship of the exchange rate, inflation rate, interest rate and money supply in Malaysia for 35 years from the period 1980 to 2014. The relationship is examined by undertaking regression analysis using time series data from 1980 to 2014 that collected from International Financial Statistics. The purpose of the study is to see the relationship and effect among the selected variables whether the relationship is positive or negative by using Multiple Linear Regression, the model are tested by using E-Views software. From the result of Multiple Linear Regression, the study shows that inflation rate has no significant effect towards exchange rate in Malaysia. Meanwhile, interest rate and money supply has a significant relationship towards exchange rate in Malaysia.